The Vir Tricultus: an investigation of the classical, Jewish and Christian influences on Jerome's translation of the Psalter Iuxta Hebraeos - Cameron, J (2006)
This thesis investigates the influences on Jerome's translation of the Psalter from the Hebrew (IH Psalter) that came from the three major socio-religious spheres with which Jerome was acquainted. It argues that the results offer insights into Jerome's conception of the nature of Hebrew text itself, of the relationship between it and the Christian faith, and of his role as translator. The thesis argues and demonstrates that the language of the IH Psalter reveals influences that derive from Jerome's classical background, from his contact with rabbinic scholars in Palestine, and, especially, from his adopted Christian faith. These influences are subtle, but their combined effect is considerable. Care is taken to demonstrate that Jerome was a competent translator, and that he deliberately intended the classical, Jewish or Christian nuances that are discussed. This is achieved, first, by comparing the IH Psalter with the Hebrew as an initial step, then with Jerome's translation of the Psalter from the Hexaplaric Septuagint, and with the various Greek versions where they are extant; and second, by evaluating the relationship between Jerome's translations and his exegetical material on the Psalter. The fact that Jerome is both translator and exegete of the Psalter allows clear insight into the impact of his understanding of the Psalms on his translation of them. The Conclusion argues that the issues can be focussed on and find their resolution in Jerome's conception of the nature and function of the Hebrew text. By imputing to Jerome a belief in the divine inspiration of the Hebrew text, and a belief that the Hebrew text properly understood and properly translated reveals Jesus Christ, the character of the IH Psalter can best be explained. Jerome's translations often exploited available linguistic space, but they rarely went beyond what hebraica veritas could reasonably signify.